Digital Mapping of Dukuh Village’s Potential, Banyudono Subdistrict, Boyolali Regency - Noviani, Rita; Nugraha, Setya; Tjahjono, Gentur Adi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Law Number 6 of 2014 concerning Villages provides opportunities for villages to develop according to their potential. Development in Dukuh Village had not been supported by digital geospatial information data. Digital mapping of village potentials needs to be carried out for more optimal utilization of village potentials to support sustainable development. This activity aimed to educate village officials and community representatives (Head RT/RW and Bumdes) in making digital maps of the village's potential web-based so that it could be easily accessible and developed, which could also be a supporting data for the village development policies of the Dukuh Village. The activities of the community service program were held from April to September 2021. The methods used were field surveys, data processing, outreach, training, and mentoring. Questionnaires were given to students before and after the training. The data were analyzed using quantitative descriptive technique. The entire program successfully increased the knowledge and skills of the village officials in making digital maps of the potential in Dukuh Village. Posttest results of more than 70% of the 28 participants show that they managed to acquire digital map knowledge and skills. Village officials became able to make digital maps using WebGIS very well in the fields of agriculture, livestock, and plantations. The digital map they created could provide data and information for planning the development of the agricultural, livestock, and plantation sectors in Dukuh village.